A study on the customer’s satisfaction towards visa and mastercard/ Iskandar Hj.Arabi - Hj.Arabi, Iskandar (2004)
Bank Simpanan Nasional is committed to delivering the best to its customers. Its committed employees, quality processes, customer service excellence and favorable brand image support this mission. The customers will vary in-how they define excellent or better quality of products. Keeping this in mind, this research aims to study the level of customer’s satisfaction towards Visa and MasterCard at Bank Simpanan Nasional before appropriate recommendations can be made. The study is confined to the account holders of Bank Simpanan Nasional,Sibu only.